2017
DOI: 10.1071/ah15218
|View full text |Cite
|
Sign up to set email alerts
|

Private general paediatric care availability in Melbourne

Abstract: Objective The aims of the present study were to determine the actual availability of private general paediatric appointments in the Melbourne metropolitan region for children with non-urgent chronic illnesses and the cost of such care. Methods A 'secret shopper' method was used. Telephone calls were made to a random sample of 47 private paediatric clinics. A trained research assistant posed as a parent, requesting the first available appointment with a specific paediatrician. Data regarding appointment availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…This finding of reduced use of specialists in Australia is consistent with Medicare data for older children in LSAC who are disadvantaged 16. It has been well documented that there are long waiting lists to see publicly funded paediatricians, and wide variation in billing and out-of-pocket expenses for private paediatricians 37…”
Section: Discussionsupporting
confidence: 80%
“…This finding of reduced use of specialists in Australia is consistent with Medicare data for older children in LSAC who are disadvantaged 16. It has been well documented that there are long waiting lists to see publicly funded paediatricians, and wide variation in billing and out-of-pocket expenses for private paediatricians 37…”
Section: Discussionsupporting
confidence: 80%
“…This finding regarding reduced access to specialists in Australia is consistent with Medicare data for older children in LSAC (16). It has been well documented that there are long waiting lists to see publicly funded paediatricians and wide variation in billing and out of pocket expenses for private paediatricians (32). This is a concerning finding in terms of the important role that paediatricians play in diagnostic evaluation, assessment of underlying causes and comorbidity and access to funding schemes including Carer's Allowance, the National Disability Insurance Scheme and Australia's funding model to provide early intervention to children who are developmentally vulnerable (33).…”
Section: Use Of Any Health Services By Developmental Vulnerability Ansupporting
confidence: 81%
“…Within the last 10 years, only one other secret shopper study has investigated wait times for private paediatricians in Australia. 9 This study reported a 33-day average wait time for a child with a medical condition. However, consistent with our finding of a 44-day average wait time, paediatricians report that they usually see children with medical conditions sooner than children with developmental and behavioural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There is a scarcity of Australian data on wait times and costs for children to see a private mental health specialist. Kunin, Allen 9 found the average wait time for a general paediatric appointment in metropolitan Melbourne was 33 days with an out-of-pocket cost of $128. However, in Kunin et al's study the appointments were for physical health complaints (i.e.…”
Section: What This Paper Addsmentioning
confidence: 99%